Neurotrophins and neuropeptides as inflammatory mediators in case of chronic dermatosis - A. A. Kubanova; V. A. Smolyannikova; V. V. Chikin; A. E. Karamova (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
This literature review examines the role of neurotrophins and neuropeptides for the development of skin inflammatory reactions in case of chronic inflammatory dermatoses. The article describes inflammatory effects of neurotrophin, a nerve growth factor, neuropeptide substance P and calcitonin gene-related peptide. Factors affecting the condition of skin innervation and development of inflammation - neurotrophin, a nerve growth factor, amphiregulin, an epidermal growth factor, and semaphorin 3A, a nerve repulsion factor - were examined. Searching for and administering antagonists of proinflammatory effects of neuropeptides, neurotrophins and epidermal growth factor can become new approaches to the treatment of chronic inflammatory dermatoses.